Translation and psychometric evaluation of the persian version of the "Nursing Profession Self-Efficacy Scale" - Zahra Lazemi; Maasoumeh Barkhordari-Sharifabad (BMC, 2023)
Abstract Background Self-efficacy demonstrates the general competence of nurses in providing nursing care. Evaluation of nurses' self-efficacy is of particular importance to improve nursing care. The existing self-efficacy scales in Iran are insufficient due to lack of focus on the specific issues of the nursing profession. This study was conducted with the aim of translating and psychometrically evaluating the Persian version of "Nursing Profession Self-Efficacy Scale" (NPSES). Materials and method This cross-sectional study was conducted in two parts: translation and psychometric evaluation. After getting permission from the original developer of the scale, the process of translating the questionnaire into Persian was done based on the Polit and Yang model. Then, the face validity was explored using a qualitative method with the participation of 10 nurses. The content validity was investigated using a qualitative and quantitative method (content validity index) with the participation of 15 experts. Construct validity was surveyed with exploratory and confirmatory factor analysis via completing the questionnaire by 550 nurses worked in different wards of hospitals affiliated to Shahid Sadoughi University of Medical Sciences, Yazd/Iran, who were selected using convenience sampling. The reliability of the tool was also established with internal consistency and stability methods, with the participation of 30 nurses. SPSS20 and AMOS were used for data analysis. Results "Nursing Profession Self-Efficacy Scale" includes 19 items for which the translation and cultural compatibility of the Persian version were confirmed. Face validity and content validity (SCVI/Ave = 0.9) were acceptable. By conducting exploratory factor analysis, three factors (professional situation, care situation, and support situation) were identified, which accounted for 62.38% of the variance of the scores. In the confirmatory factor analysis, the values of the fit indices confirmed the appropriate fit of the model. The reliability was established using Cronbach's α method (α = 0.86) and an ICC of 0.83, indicating that the scale was reliable. Conclusion The translation, validity, and reliability of the Persian version of "Nursing Profession Self-Efficacy Scale" suggested that this tool has a clear and legitimate translation. Also, this tool has good validity and reliability and can be used as one of the tools to measure the self-efficacy of Iranian nurses.